Metastatic breast cancer patients treated with low-dose metronomic chemotherapy with cyclophosphamide and celecoxib: clinical outcomes and biomarkers of response - Perroud, Herman A (2016)
Fil: Fil: Perroud, Herman A. Institute of Experimental Genetics. School of Medical Sciences. National University of Rosario; Rosario; Argentina